E-cadherin induces mesenchymal-to-epithelial transition in human ovarian surface epithelium - Auersperg, Nelly (The National Academy of Sciences, 1999)
Ovarian carcinomas are thought to arise in the ovarian surface epithelium (OSE). Although this tissue forms a simple epithelial covering on the ovarian surface, OSE cells exhibit some mesenchymal characteristics and contain little or no E-cadherin. However, E-cadherin is present in metaplastic OSE cells that resemble the more complex epithelia of the oviduct, endometrium and endocervix, and in primary epithelial ovarian carcinomas. To determine whether E-cadherin was a cause or consequence of OSE metaplasia, we expressed this cell-adhesion molecule in simian virus 40-immortalized OSE cells. In these cells the exogenous E-cadherin, all three catenins, and F-actin localized at sites of cell–cell contact, indicating the formation of functional adherens junctions. Unlike the parent OSE cell line, which had undergone a typical mesenchymal transformation in culture, E-cadherin-expressing cells contained cytokeratins and the tight-junction protein occludin. They also formed cobblestone monolayers in two-dimensional culture and simple epithelia in three-dimensional culture that produced CA125 and shed it into the culture medium. CA125 is a normal epithelial-differentiation product of the oviduct, endometrium, and endocervix, but not of normal OSE. It is also a tumor antigen that is produced by ovarian neoplasms and by metaplastic OSE. Thus, E-cadherin restored some normal characteristics of OSE, such as keratin, and it also induced epithelial-differentiation markers associated with weakly preneoplastic, metaplastic OSE and OSE-derived primary carcinomas. The results suggest an unexpected role for E-cadherin in ovarian neoplastic progression.